Development of a Scientific Literacy Test Instrument to Identify Students' Understanding of Concepts and Misconceptions in Colloidal Systems Material - Windani, Shelley Rifda (Chemistry in Education, 2024)
Literacy is one of the skills that need to be considered in the 21st century. This study aims to develop a literacy test instrument to determine students' understanding of concepts and misconceptions on colloidal material using a valid three-tier multiple choice test instrument based on expert validation and Rasch analysis. The research method used is 4D (Define, Design, Development, and Desimination). Research data collection techniques through observation, tests, interviews, and questionnaires. The results of Rach's analysis showed a value of 0.75 (sufficient). The quality of the developed instrument resulted in 13 valid questions. The level of difficulty obtained is 3 points of the easy category, 7 points of the medium category, 4 points of the difficult category, and 6 points of the very easy category. The highest concept understanding of students in the submaterial understanding solutions, colloids, and suspensions with a percentage of 77% and the highest misconception of students in the submaterial of categorizing experimental designs involving colloidal principles with a percentage of 38%. The results of the recapitulation of the response questionnaire obtained by 91% of students gave affirmative responses to the instrument developed. Based on the results of the study, the developed test instruments are feasible for the analysis of students' understanding of concepts and misconceptions.